CIRCULAR ECONOMY EDUCATION: EXPERIENCE OF FINLAND - Sysoiev, Oleksii (The Modern Higher Education Review, 2021)
Since the announcement of the National economic strategy 2030, the transition to a circular economy has become an agenda for Ukraine. In these conditions searching for good experience and practices is an essential priority for national higher education. The research focuses on analysing educational experience in the circular economy in the Republic of Finland. The Republic of Finland has become the first country to provide degree programmes in the circular economy. This theoretical research is based in particular on literature review as well as analysis of Finnish universities websites for studying the degree programmes (their learning content and structure), methods and forms of education. The article presents a generalised analysis of the bachelor, master and doctoral programmes in the circular economy or related sciences. The main findings are methods of education in circular economy distinguished according to the following principles: historical (project-based), priority in the pedagogy implementation (teaching and learning), students activities (combined methods), teaching strategies (heuristic methods), source of knowledge (direct or indirect study of reality). The project-based method dominates when a multidisciplinary student team designs the project. The education format varies from traditional to online.